Heparin-binding epidermal growth factor (EGF)-like growth factor in pediatric patients with type 1 diabetes mellitus. (3rd March 2020) - Kacarevic, Dragana; Bogavac-Stanojevic, Natasa; Spasojevic-Kalimanovska, Vesna; Bojanin, Dragana; Milenkovic, Tatjana; Stefanovic, Aleksandra; Mihajlovic, Marija; Vujcic, Sanja; Vukovic, Rade; Zeljkovic, Aleksandra; Kotur-Stevuljevic, Jelena; Mazibrada, Ilijana; et al.
Abstract: Heparin-binding EGF-like growth factor (HB-EGF) is involved in atherosclerosis progression. We investigated association between plasma HB-EGF levels and lipid, oxidative stress and inflammatory biomarkers in pediatric patients with type 1 diabetes mellitus (T1DM). Levels of HB-EGF, high-sensitive C-reactive protein (hsCRP), prooxidant-antioxidant balance (PAB), total antioxidant status (TAS), oxidized low-density lipoproteins (oxLDL), metabolic control and serum lipid parameters and paraoxonase 1 (PON1) activity were determined in 74 patients and 40 controls. In comparison to controls, patients had significantly higher levels ( p  < 0.01) of HB-EGF, hsCRP, PAB and oxLDL particles ( p  < 0.001), but lower levels of TAS and PON1 activity. In T1DM group, HB-EFG levels were positively associated with hsCRP, PAB and oxLDL levels. hsCRP and oxLDL levels were independent predictors of HB-EGF concentration. We demonstrated that oxidative modifications of LDL particles and low-grade inflammation are main determinants of increased plasma HB-EGF levels, which indicates an interactive role of oxidative stress, dyslipidemia and inflammation.